Platelets and cardiovascular risk. Issue 1 (2nd January 2017) - Renga, Barbara; Scavizzi, Franco
Abstract: Atherosclerosis and its late sequels are still the number one cause of death in Western societies. Platelets are a driving force not only during the genesis of atherosclerosis, but especially in its late stages, as evidenced by complications such as arterial thrombosis, myocardial infarction, and ischaemic stroke. Platelets are small, anucleate blood elements of critical importance in cardiovascular disease, a major cause of morbidity and mortality. Numerous risk scores exist to identify healthy individuals at increased risk of developing atherosclerosis and cardiovascular disease. However, markers of cardiovascular risk not routinely assessed (i.e. platelet activity, mean platelet volume and P- selectin) may also contribute to be useful in calculating cardiovascular risk. The present review and meta-analysis summarizes the evidence for measuring platelet function indices to identify patients at risk of developing cardiovascular events.